ASAS KEMANFAATAN DALAM TARIF PROMOSI YANG DIPERGUNAKAN OLEH GRAB INDONESIA BERDASARKAN KEPUTUSAN MENTERI PERHUBUNGAN NO 348 TAHUN 2019 TENTANG PEDOMAN PERHITUNGAN BIAYA JASA PENGGUNAAN SEPEDA MOTOR YANG DIGUNAKAN UNTUK KEPENTINGAN MASYARAKAT YANG DILAKUKAN DENGAN APLIKASI - Hasian Doli; Siti Nurbaiti (Fakultas Hukum Universitas Tarumanagara, 2020)
Globalization brings changes to the progress of science and technology, especially in the field of transportation. Promotion as one of the marketing strategies has taken a big part in attracting the hearts and loyalties of public transport users to move to modern online-based transportation users. Effectiveness and efficiency are the main choices of the community in determining the mode of transportation given the high mobility in the community, especially the capital society. The transition of modes of transportation from conventional transportation to online transportation has caused various problems in the community, one of which did not reach the principle of usability in its implementation because promotional tariffs provided by online transportation service providers are too cheap. The government has issued Minister of Transportation Decree No. 348 in 2019 with the aim of reducing the risk of unfair business competition between driver partners and the realization of the principle of expediency. The existence of regulations governing upper and lower limit tariffs aims to create the principle of benefits as contained in the transportation law.